Formation Producing Control of Multi-Quadcopter Systems Under the Cloud Access - Nargess Sadeghzadeh-Nokhodberiz; Mohammad-Reza Ghahramani-Tabrizi; Allahyar Montazeri (IEEE Access)
The use of cloud-connected UAV swarm plays an important role in the future of mobility. One of the challenges to address before realising this technology is achieving a formation producing control of quadcopter swarms under the cloud access. For this purpose, the problem of cloud-based formation control for a nonlinear 6-DOF under-actuated multi-quadcopter system is studied in this paper. This is different compared to the existing literature, studying the rendezvous problem for a second-order multi-agent system. As the first step, a hierarchical control structure is provided to derive the control laws and conditions for the stability of the nonlinear under-actuated multi-quadcopter system to guarantee the asymptotic consensus of the quads’ positions to the biased average of the initial positions. Then, the control laws are extended and derived under the cloud access condition and the stability proofs are analysed for the quadcopters’ dynamics. The results guarantee the practical consensus of the quadcopter system to the biased position of their initial values. Toward this, a scheduling rule for the access to the cloud is designed and it is shown that the rule avoids the Zeno behavior.For this purpose, upper bounds on the control laws of the cloud-connected neighboring agents between two consecutive connections of each agent are considered. The numerical results verify the efficacy of the proposed method.